Jawabanmu

2014-03-26T10:04:01+07:00
1. a. (fog) (x) = f(g(x))
                   = f (x+3)
                   = x² (x+3)-4
                   = 2x² + 3x² - 4
                   = 5x^4 - 4
     b. (gof) (x) = g (x² - 4)
                     = x (x² - 4) +3
                     = 2x² - 4x + 3
                     = -2x² + 3
2.  a. (fog) (x) = f ( g (x) )
                    = f ( x² + 2 )
                    = x² (x² + 2) - 6
                    = x^4 + 2x² - 6
                    = 3x^8 - 6
     b. (gof) (x) = g(x² - 6)
                    = x² (x² - 6) + 2
                    = x^4 - 6x² +  2
                     = -5x^8 + 2